Effect of Porogen on the Catalytic Activity of Molecular Imprinted Polymers - Deepthi, K.P.; Mathew, Beena (Asian Journal of Chemistry, 2012)
A synthetic polymer catalyst was designed and synthesized for enhancing the rate of the hydrolysis reaction of Z-L-phenylalanine-PNP ester. Transition state analogues for the ester hydrolysis reaction pathways were used as templates for the synthesis of molecular imprinted N-methacryloyl L-histidine(MAH)-ethylene glycol dimethacrylate copolymers. Catalytic studies revealed that the imprinted polymers were selective for the transition state analogue corresponding to the template used in the polymer synthesis. Substrate hydrolysis was measured under pseudo first order reaction conditions (rate constant k). The rates of transition state analogue imprinted polymer catalyzed reactions were compared with those carried out in acetonitrile-Tris HCl buffer solution of pH 7.25 at room temperature as well as to the rate of reaction in the presence of non-imprinted polymer. In order to provide comparison between effect of a thermodynamically stable and an unstable solvent on the morphology of the polymer matrix and its catalytic activity the polymerization was carried out using DMSO and chloroform as the porogen. The catalytic activity of the transition state analogue imprinted polymer is found to be substrate specific, solvent and pH dependent. The molecular imprinted polymer synthesized in DMSO showed high selectivity supporting that the nature of the porogen has an effect on the hydrolysis by transition state analogue imprinted catalysts.